2017
DOI: 10.1016/j.seizure.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in tuberous sclerosis patients in Sweden – Healthcare utilization, treatment, morbidity, and mortality using national register data

Abstract: The prevalence of epilepsy in this study was in the lower range of previously reported numbers, suggesting that epilepsy may be overestimated in non-population based studies. A substantial part of the healthcare utilization was directly related to epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
51
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 23 publications
13
51
2
1
Order By: Relevance
“…Overwater et al (2015) used several different AEDs, such as VPA, LEV, and VGB, with VPA being the most frequently prescribed first treatment. Similar data have been obtained in a Swedish study where VPA, CBZ, LTG, LEV, and TPM were the most commonly prescribed drugs (Welin et al, 2017). Similar data have been obtained in a Swedish study where VPA, CBZ, LTG, LEV, and TPM were the most commonly prescribed drugs (Welin et al, 2017).…”
Section: The Most Effective Aeds Appeared To Be Carbamazepine (Cbz) Andsupporting
confidence: 82%
See 1 more Smart Citation
“…Overwater et al (2015) used several different AEDs, such as VPA, LEV, and VGB, with VPA being the most frequently prescribed first treatment. Similar data have been obtained in a Swedish study where VPA, CBZ, LTG, LEV, and TPM were the most commonly prescribed drugs (Welin et al, 2017). Similar data have been obtained in a Swedish study where VPA, CBZ, LTG, LEV, and TPM were the most commonly prescribed drugs (Welin et al, 2017).…”
Section: The Most Effective Aeds Appeared To Be Carbamazepine (Cbz) Andsupporting
confidence: 82%
“…This was also the most frequently used drug in infants presenting with focal seizures. Similar data have been obtained in a Swedish study where VPA, CBZ, LTG, LEV, and TPM were the most commonly prescribed drugs (Welin et al, 2017). Recently, also Lacosamide appeared to be an effective and safe treatment of refractory focal onset seizures in TSC (Geffrey, Belt, Paolini, & Thiele, 2015).…”
Section: Post-seizure Treatment Of Epilepsysupporting
confidence: 78%
“…Subependymal giant cell astrocytomas (SEGAs) were found in 24.4% of the TOSCA population. SEGA can obstruct the intraventricular space and lead to noncommunicating hydrocephalus requiring surgery (22.4% of those [20][21][22][23][24][25] The prevalence rate (32.9%, 35.9%) of pharmacoresistant epilepsy is similar to general population with focal epilepsy [26,27]. A mutation in the TSC2 gene is a risk factor for infantile spasms (47.3% vs. 23% with TSC1 in TOSCA) as well as an earlier manifestation of epilepsy, a higher seizure frequency, and pharmacological refractoriness [28].…”
Section: Neurological Manifestationsmentioning
confidence: 97%
“…In general, children were most frequently seen by neurologists, pediatricians, and ophthalmologists, adult patients most often visited neurologists, psychiatrists, and dermatologists, probably reflecting the changing clinical course of TSC throughout life [23]. In Swedish individuals with TSC [27], almost all (87.8%) of the study participants had experienced an outpatient visit with an International Classification of Disease 10th Edition (ICD-10) code identifying epilepsy.…”
Section: Health Care Resource Usementioning
confidence: 99%
“…Understanding the epidemiology and disease burden of TSC is crucial for better management of the TSC population (20). Six population-based studies regarding the prevalence and mortality of TSC in the recent 15 years can be found (Table 1) (12,(21)(22)(23)(24)(25)(26). Amongst the six studies, three studies feature the prevalence of TSC in Caucasian population, with variable prevalence rate (ranges from 1 in 7,872 to 1 in 24,956).…”
Section: Introductionmentioning
confidence: 99%